PENERAPAN ASAS KEPASTIAN HUKUM DALAM PUTUSAN PENGADILAN PAJAKATAS SENGKETA PENGEMBALIAN BIAYA OPERASI - Pawoko, Sigit Ibnu; Khalimi, Khalimi; Hakim, Nur (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
This study aims to analyze the impact of the Tax Court's decision on the dispute over the return of operating costs (cost recovery) in the Oil and Gas Production Sharing Contract between the Indonesian Government and the Oil and Gas Contractor. The method used in this study is normative legal research by focusing on the analysis of written legal norms such as the Oil and Gas Law, Income Tax Law, Oil and Gas Production Sharing Contracts, and Tax Court Decisions. The research approach used is the statute approach and the case study approach. The results of the study indicate that the Production Sharing Contract has regulated the cost recovery guidelines that can be returned by the Oil and Gas Contractor in connection with upstream oil and gas business activities in Indonesia, so that taxpayers are entitled to the burden of the cost recovery costs. The implementation of cost recovery burdens in tax reporting by Upstream Oil and Gas Companies is in accordance with the Production Sharing Contract, the principle of legal certainty and the principle of uniformity in the upstream oil and gas industry. To improve legal certainty and avoid negative impacts on upstream oil and gas investment in Indonesia, recommendations can be made for solutions to revise and harmonize regulations, improve tax authorities' knowledge of upstream oil and gas business patterns, and create more detailed technical guidelines for the implementation of cost recovery to provide legal certainty for Oil and Gas Contractors